Polycarbonate resin and optical member using same
By adjusting the molar ratio and molecular weight of the units in the polycarbonate resin, its flowability and optical properties are optimized, solving the problem of existing resins in molding thin-walled optical components, and achieving the effects of high Abbe number, low orientation birefringence and high glass transition temperature.
Patent Information
- Application Number
- CN202480028167.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-25
- Filing Date
- 2024-04-15
- Publication Date
- 2025-11-25
AI Technical Summary
Existing polycarbonate resins are difficult to mold when forming thin-walled optical components. They have high orientation birefringence, high photoelasticity, low refractive index and glass transition temperature, and are not suitable for injection molding.
By controlling the molar ratio and weight-average molecular weight of the units represented by formula (1) and/or formula (2) to the units represented by formula (3) in the polycarbonate resin, the orientation birefringence, photoelastic coefficient, refractive index and glass transition temperature are optimized to prepare polycarbonate resins with a weight-average molecular weight of 10,000 to 55,000.
This invention achieves excellent fluidity, low orientation birefringence, high Abbe number, low photoelasticity, and high refractive index and glass transition temperature in polycarbonate resins, making them suitable for thin-walled optical components such as imaging lenses.
Smart Images

Figure CN121013877A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to polycarbonate resins and optical components using the resin. Background Technology
[0002] Glass, traditionally used as a material in optical systems, can achieve the required optical properties and has excellent environmental resistance, but it suffers from poor processability. In contrast, resin, which is cheaper and has better processability than glass, is increasingly being used in optical components.
[0003] Patent document 1 describes an optical lens with high refractive index and low orientation birefringence made of polycarbonate resin having a structure of pentacyclic pentadecanediethanol (hereinafter sometimes referred to as PCPDM) and 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene (hereinafter sometimes referred to as BPEF).
[0004] Furthermore, in the optical design of optical units, it is known to correct chromatic aberration by combining multiple lenses with different Abbe numbers. For example, chromatic aberration can be corrected by combining a lens made of alicyclic polyolefin resin with a low refractive index and high Abbe number with a lens made of polycarbonate resin composed of bisphenol A (nd = 1.59, νd = 31) with a high refractive index and low Abbe number. In recent years, resins with high refractive index and low Abbe number have been actively developed, and consequently, the demand for resins with high Abbe number is also increasing. In addition, polycarbonate resins derived from bisphenol A, obtained by reacting 2,2-bis(4-hydroxyphenyl)propane (commonly known as bisphenol A) with phosgene or carbonate, have excellent heat resistance and transparency, as well as excellent mechanical properties such as impact resistance. Therefore, they are widely used as optical materials, not only as structural materials but also as optical materials in optical disc substrates, various lenses, prisms, and optical fibers. However, polycarbonate resins derived from bisphenol A have problems with large birefringence due to molecular orientation and residual stress during molding. Therefore, with the expanding applications of optical materials in recent years, there is a strong demand for further development of materials with low birefringence. For example, Patent Document 2 describes a polycarbonate resin with a high Abbe number but low photoelasticity coefficient, obtained by copolymerizing bisphenol A with PCPDM. Furthermore, Patent Document 3 proposes a method for manufacturing carbonate derivatives without the use of alkali by photoreacting halomethane with a specific amount of hydroxyl-containing compound in the presence of oxygen, and exemplifies a copolymer of BPEF and PCPDM as an example of its manufacture.
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: Japanese Patent Application Publication No. 2005-241962
[0008] Patent Document 2: Japanese Patent Application Publication No. 2000-302860
[0009] Patent Document 3: WO2020 / 100977 Summary of the Invention
[0010] However, the polycarbonate resin with the aforementioned PCPDM and BPEF structure is difficult to mold when applied to thin-walled optical components such as imaging lenses, and its oriented birefringence requires further improvement. Furthermore, the polycarbonate resin composed of bisphenol A and PCPDM has the following drawbacks: there is room for improvement in the photoelastic coefficient, it has high oriented birefringence, and its refractive index and glass transition temperature are low. In addition, the resulting resin has a high molecular weight, making it unsuitable for injection molding applications and unsuitable for thin-walled optical components such as imaging lenses. Moreover, the weight-average molecular weight of the aforementioned BPEF and PCPDM copolymer polycarbonate is extremely low at 3360, which is insufficient for use as a structural or optical material.
[0011] Therefore, the first objective of this invention is to provide a polycarbonate resin with excellent flowability and low orientation birefringence.
[0012] A second objective of the present invention is to further provide a polycarbonate resin with high Abbe number, oriented birefringence, and low photoelasticity, based on the first objective.
[0013] A third objective of the present invention is to further provide a polycarbonate resin with low orientation birefringence, high refractive index, and high glass transition temperature, based on the first objective.
[0014] The inventors have discovered that the above-mentioned problems can be solved by the present invention having the following aspects.
[0015] That is, the present invention is as follows.
[0016] Method 1
[0017] A polycarbonate resin comprising units represented by formula (1) and / or formula (2) and units represented by formula (3), having a weight-average molecular weight Mw of 10,000 to 55,000.
[0018]
[0019] (where R) 1 ~R 4 Each can independently represent a hydrogen atom or a hydrocarbon group with 1 to 10 carbon atoms.
[0020] Method 2
[0021] According to the polycarbonate resin of method 1, wherein R in formula (3) above... 1 ~R 4 It is a hydrogen atom.
[0022] Method 3
[0023] The polycarbonate resin according to method 1 or 2, wherein the molar ratio of the unit represented by formula (1) and / or formula (2) to the unit represented by formula (3) is 99:1 to 1:99.
[0024] Method 4
[0025] According to the polycarbonate resin of method 3, the molar ratio of the unit represented by formula (1) and / or formula (2) to the unit represented by formula (3) is 65:35 to 35:65.
[0026] Method 5
[0027] According to the polycarbonate resin of method 1 or 2, the absolute value of the oriented birefringence is 7.0 × 10⁻⁶. -3 the following.
[0028] Method 6
[0029] According to method 1 or 2, the polycarbonate resin wherein the photoelastic modulus is less than 35 × 10⁻⁶. -12 Pa.
[0030] Method 7
[0031] The polycarbonate resin according to method 1, wherein all repeating units contain more than 50 mol% of units represented by formula (1) and / or formula (2), and the weight-average molecular weight Mw is 10,000 to 50,000.
[0032] Method 8
[0033] The polycarbonate resin according to method 7, wherein the repeating units contain more than 0% and less than 50 mol% of the unit represented by formula (3).
[0034] Method 9
[0035] According to the polycarbonate resin of method 7 or 8, the molar ratio of the unit represented by formula (1) and / or formula (2) to the unit represented by formula (3) is 99:1 to 50:50.
[0036] Method 10
[0037] The polycarbonate resin according to method 7 or 8, wherein the photoelastic modulus is less than 25 × 10⁻⁶. -12 Pa.
[0038] Method 11
[0039] The polycarbonate resin according to method 7 or 8, wherein the Abbe number is 25.0 or higher.
[0040] Method 12
[0041] The polycarbonate resin according to method 1, wherein the total repeating units contain more than 0% and less than 50 mol% of units represented by formula (1) and / or formula (2), and the weight-average molecular weight Mw is 10,000 to 50,000.
[0042] Method 13
[0043] The polycarbonate resin according to method 12, wherein more than 50 mol% of the unit represented by formula (3) is included in all repeating units.
[0044] Method 14
[0045] The polycarbonate resin according to method 12 or 13, wherein the molar ratio of the unit represented by formula (1) and / or formula (2) to the unit represented by formula (3) is 1:99 to 49:51.
[0046] Method 15
[0047] According to the polycarbonate resin of method 12 or 13, the absolute value of the oriented birefringence is 3.0 × 10⁻⁶. -3 the following.
[0048] Method 16
[0049] The polycarbonate resin according to method 12 or 13, wherein the refractive index nd is 1.600 or higher.
[0050] Method 17
[0051] The polycarbonate resin according to method 12 or 13, wherein the glass transition temperature is above 140°C.
[0052] Method 18
[0053] An optical component comprising a polycarbonate resin according to any one of methods 1, 2, 7 or 12.
[0054] Method 19
[0055] The optical component according to method 18 is an imaging lens or a sensor camera lens.
[0056] Method 20
[0057] The imaging lens or sensor camera lens according to method 19, wherein the thickness of the central portion is 0.05 to 3.0 mm.
[0058] The polycarbonate resin of this invention exhibits excellent flowability and low orientation birefringence. Therefore, it can be well used in thin-walled optical components such as imaging lenses, resulting in significant industrial benefits.
[0059] Furthermore, the preferred polycarbonate resin of the present invention has a high Abbe number and low orientation birefringence and photoelastic coefficient.
[0060] Furthermore, the polycarbonate resin of the present invention exhibits low orientation birefringence, high refractive index, and high glass transition temperature. Thus, the polycarbonate resin of the present invention provides significant industrial benefits. Detailed Implementation
[0061] The present invention will be described in further detail below.
[0062] Implementation Method 1
[0063] <Polycarbonate resin>
[0064] A polycarbonate resin comprising units represented by formula (1) and / or formula (2) and units represented by formula (3), having a weight-average molecular weight Mw of 10,000 to 55,000 or less.
[0065] The polycarbonate resin of the present invention comprises units represented by formula (1) and / or formula (2) and units represented by formula (3). All repeating units contain more than 0 mol% and less than 100 mol% of units represented by formula (1) and / or formula (2), and also contain more than 0 mol% and less than 100 mol% of units represented by formula (3). The units represented by formula (1) and / or formula (2) are preferably 10 mol% or more, more preferably 20 mol% or more, and even more preferably 35 mol% or more in all repeating units. Furthermore, the units represented by formula (1) and / or formula (2) are preferably 90 mol% or less, more preferably 80 mol% or less, and even more preferably 65 mol% or less in all repeating units. Within the above ranges, the orientation birefringence is low, and the balance between refractive index, Abbe number, and photoelastic coefficient is excellent. Furthermore, the molar ratio of the unit represented by formula (1) and / or formula (2) to the unit represented by formula (3) is preferably 99:1 to 1:99, more preferably 80:20 to 20:80, and even more preferably 65:35 to 35:65. If the unit represented by formula (1) and / or formula (2) and the unit represented by formula (3) are within the above range, the orientation birefringence is small, and the balance between refractive index, Abbe number and photoelastic coefficient is excellent.
[0066] It should be noted that in the above-mentioned mole % and mole ratio, the so-called unit represented by formula (1) and / or formula (2) represents the total unit of formula (1) and formula (2) when the polycarbonate resin contains the unit represented by formula (1) and formula (2), and represents the unit of either formula (1) or formula (2) when it contains either the unit represented by formula (1) or formula (2).
[0067]
[0068] (where R) 1 ~R 4 Each can independently represent a hydrogen atom or a hydrocarbon group with 1 to 10 carbon atoms.
[0069] The polycarbonate resin of the present invention has a weight-average molecular weight (Mw) of 10,000 or more, preferably 15,000 or more, and more preferably 20,000 or more. If the weight-average molecular weight (Mw) is 10,000 or more, it has sufficient mechanical strength as a structural material or optical material, which is preferable. Furthermore, the weight-average molecular weight (Mw) is 55,000 or less, more preferably 50,000 or less, further preferably 40,000 or less, particularly preferably less than 35,000, and most preferably 30,000 or less. If the weight-average molecular weight (Mw) is 55,000 or less, it exhibits excellent flowability during injection molding, which is therefore preferable. In particular, when the polycarbonate resin of the present invention is used in thin-walled optical components such as imaging lenses, it exhibits excellent flowability, which is therefore preferable. The weight-average molecular weight (Mw) can be determined by GPC using polystyrene with a known molecular weight as a standard sample and chloroform as the developing solvent.
[0070] The absolute value of the orientation birefringence of the polycarbonate resin of the present invention is preferably 7.0 × 10⁻⁶. -3 Below. If the absolute value of orientation birefringence is below the above, birefringence caused by molecular orientation is less likely to occur, and therefore is preferred. Orientation birefringence is measured at a wavelength of 589 nm after cutting a 70 mm long (45 mm between fixtures) and 15 mm wide test piece from a 100 μm thick cast film made of polycarbonate resin, stretching it twice at Tg + 10 °C.
[0071] The photoelastic modulus of the polycarbonate resin of the present invention is preferably less than 35 × 10⁻⁶. -12 Pa. If the photoelasticity coefficient is within the above range, stress-induced birefringence is less likely to occur, and therefore it is preferred. The photoelasticity coefficient was measured using a Spectroellipsometer M-220 manufactured by Nippon Spectrophotometer Co., Ltd., on a test piece cut from a 100 μm thick cast film of polycarbonate resin with a length of 50 mm and a width of 10 mm.
[0072] The refractive index nd of the polycarbonate resin of the present invention, measured at a temperature of 20°C and a wavelength of 587.56 nm, is preferably 1.540 or higher. If the refractive index is above this value, the optical components can be thinned, which is therefore preferable. Alternatively, the refractive index nd can be 1.650 or lower. If the refractive index nd is within this range, the degree of freedom in optical design is increased when multiple lenses are used in combination, which is also preferable.
[0073] The Abbe number of the polycarbonate resin of the present invention is preferably 25.0 or higher. If the Abbe number is higher than or equal to this value, the chromatic aberration of the optical component is reduced, which is therefore preferable. Alternatively, the Abbe number can be 57.0 or lower. If the Abbe number is within the above range, the degree of freedom in optical design is increased when using multiple lenses in combination, which is therefore preferable.
[0074] Here, the Abbe number (νd) is calculated from the refractive index at temperatures of 20°C and wavelengths of 486.13 nm, 587.56 nm, and 656.27 nm using the following formula.
[0075] νd=(nd-1) / (nF-nC)
[0076] nd refers to the refractive index at a wavelength of 587.56 nm.
[0077] nF refers to the refractive index at a wavelength of 486.13 nm.
[0078] nC refers to the refractive index at a wavelength of 656.27 nm.
[0079] The glass transition temperature of the polycarbonate resin of the present invention is preferably 130°C or higher. If the glass transition temperature is within the above range, the temperature range in which the optical component can be used becomes higher, which is therefore preferred. Alternatively, the glass transition temperature can be 160°C or lower. If the glass transition temperature is within the above range, the balance between heat resistance and moldability is excellent, which is therefore preferred.
[0080] The thermal decomposition temperature of the polycarbonate resin of the present invention is preferably 370°C or higher. If the thermal decomposition temperature is above this value, the polycarbonate resin of the present invention exhibits excellent processing stability during molding and processing, and also results in less coloring, thus it is preferred. Alternatively, the thermal decomposition temperature can be 420°C or lower. The thermal decomposition temperature can be determined by TGA (thermogravimetric analysis), and is the temperature at which a 5% weight reduction occurs.
[0081] The melt viscosity (Pa·s) of the polycarbonate resin of the present invention at 260°C and a shear rate of 1216 / sec is preferably 30 or higher. Furthermore, the melt viscosity (Pa·s) at 260°C and a shear rate of 1216 / sec is preferably 500 or lower. If the melt viscosity is within the above range, the moldability during injection molding is excellent, and therefore it is preferred. Especially when injection molding thin-walled components such as lenses, the melt viscosity during molding is very important; if the melt viscosity is within the above range, the desired lens shape can be obtained, and therefore it is preferred. The melt viscosity was measured using a Capilograph 1D manufactured by Toyo Seiki Co., Ltd. after drying the polycarbonate resin at 120°C for 4 hours.
[0082] The specific viscosity of the polycarbonate resin of the present invention is preferably 0.12 to 0.32. If the specific viscosity is 0.12 to 0.32, the balance between moldability and strength is excellent.
[0083] The specific viscosity is determined by measuring the specific viscosity (ηSP) of a solution obtained by dissolving 0.7g of polycarbonate resin in 100ml of dichloromethane at 20°C using an Ostwald viscometer, and is calculated by the following formula.
[0084] ηSP = (t - t0) / t0
[0085] [t0 is the number of seconds for the dichloromethane to fall, and t is the number of seconds for the sample solution to fall.]
[0086] In the polycarbonate resin of the present invention, R in formula (3) above 1 ~R 4 Each group can independently represent a hydrocarbon group having 1 to 10 hydrogen or carbon atoms. Examples of hydrocarbon groups include alkyl, cycloalkyl, and aryl groups.
[0087] Examples of alkyl groups include methyl, ethyl, propyl, isopropyl, butyl, tert-butyl, etc., with methyl and ethyl being preferred.
[0088] Examples of cycloalkyl groups include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, and bicyclo[1.1.1]pentyl.
[0089] Examples of aryl groups include phenyl, tolyl, naphthyl, and xylyl, with phenyl being the preferred group.
[0090] R 1 ~R 4 Each of the following is independently preferred: hydrogen atom, methyl group, phenyl group, more preferably hydrogen atom or phenyl group, and even more preferably R group. 1 and R 2 Each is independently a hydrogen atom or a phenyl group, R 3 and R 4 It is a hydrogen atom.
[0091] The repeating unit represented by formula (1) and / or formula (2) above is a repeating unit derived from pentacyclopentadecanedimethanol. In formula (1) and / or formula (2) above, it can be a pure substance or a mixture of isomers mixed in any ratio. It should be noted that pentacyclopentadecanedimethanol comprises the following structural formula.
[0092]
[0093]
[0094] The repeating unit represented by the above formula (3) is preferably a repeating unit derived from 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene or 9,9-bis[4-(2-hydroxyethoxy)-3-phenylphenyl]fluorene, and more preferably a repeating unit derived from 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene.
[0095] The polycarbonate resin of the present invention may contain repeating units other than those represented by formulas (1) to (3) above, within the scope of obtaining the advantageous effects of the present invention. Examples of dihydroxy compounds that provide such repeating units include ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, heptahydrol, octanediol, nonanediol, and tricyclic [5.2.1.0]. 2,6 Decanediethanol, Cyclohexane-1,4-diethanol, Decahydronaphthalene-2,6-diethanol, Norbornenediethanol, Cyclopentane-1,3-diethanol, Isosorbide, Isomannitol, Iso-Idole, Hydroquinone, Resorcinol, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, Bis(4-hydroxyphenyl)diphenylmethane, 1,3-bis(2-(4-hydroxyphenyl)-2-propyl)benzene, 4,4'-(3,3,5-trimethylcyclohexylene)bisphenol, 4,4'-cyclohexylene bisphenol, 4,4'-(3-methylcyclohexylene)bisphenol, bis(4-hydroxyphenyl) sulfone, bis(4-hydroxyphenyl) sulfide, biphenol, bisphenol fluorene, biscresol fluorene, 1,1'-bi-2-naphthol, 2,2'-bis(2-hydroxyethoxy)-1,1'-binaphthol, etc. Such repeating units can account for less than 30 mol% of all repeating units.
[0096] In the polycarbonate resin of the present invention, the total amount of the repeating units represented by the above formulas (1) to (3) is preferably 70 mol% or more, more preferably 80 mol% or more, and even more preferably 90 mol% or more.
[0097] The polycarbonate resin of the present invention is composed of hydroxyl or phenyl groups at its ends, and the proportion of terminal phenyl groups is preferably 70 mol% or more, more preferably 80 mol% or more, further preferably 90 mol% or more, and even more preferably 95 mol% or more.
[0098] The total light transmittance of the 1 mm thick molded body of the polycarbonate resin of the present invention is preferably 80% or more, more preferably 85% or more, and particularly preferably 88% or more. The 1 mm thick molded body can be obtained by injection molding, hot pressing, melt extrusion molding, etc., of the polycarbonate resin of the present invention.
[0099] The saturated water absorption rate of the polycarbonate resin of the present invention can be 0.10% to 0.70%, 0.20% to 0.70%, or 0.30% to 0.65%.
[0100] <Manufacturing Method of Polycarbonate Resin>
[0101] The polycarbonate resin of the present invention can be manufactured by reaction methods commonly known in the manufacture of polycarbonate resins, such as reacting carbonate precursors such as diesters with dihydroxy compounds. The basic methods of these manufacturing methods will then be briefly described.
[0102] Transesterification using diester as a carbonate precursor is carried out by heating and stirring a prescribed proportion of dihydroxy components with diester under an inert gas atmosphere, followed by distillation of the resulting alcohol or phenol. The reaction temperature varies depending on the boiling point of the alcohol or phenol produced, but is typically in the range of 120–300°C. The reaction is completed by distilling off the resulting alcohol or phenol under reduced pressure from the initial stage. Additionally, terminal stop agents, antioxidants, etc., may be added as needed.
[0103] Examples of diesters used in the above-mentioned transesterification reaction include esters of aryl and aralkyl groups with 6 to 12 substituted carbon atoms. Specifically, examples include diphenyl carbonate, xylene carbonate, bis(chlorophenyl) carbonate, and m-toluene carbonate. Diphenyl carbonate is particularly preferred. The amount of diphenyl carbonate used is preferably 0.95 to 1.10 mol relative to 1 mol of the total dihydroxy compound, more preferably 0.98 to 1.04 mol.
[0104] In addition, in melt polymerization, a polymerization catalyst can be used to accelerate the polymerization rate. Examples of such polymerization catalysts include alkali metal compounds, alkaline earth metal compounds, and nitrogen-containing compounds.
[0105] As such compounds, organic acid salts, inorganic salts, oxides, hydroxides, hydrides, alkoxides, quaternary ammonium hydroxides, etc., of alkali metals and alkaline earth metals are preferred. These compounds can be used alone or in combination.
[0106] Examples of alkali metal compounds include sodium hydroxide, potassium hydroxide, cesium hydroxide, lithium hydroxide, sodium bicarbonate, sodium carbonate, potassium carbonate, cesium carbonate, lithium carbonate, sodium acetate, potassium acetate, cesium acetate, lithium acetate, sodium stearate, potassium stearate, cesium stearate, lithium stearate, sodium borohydride, sodium benzoate, potassium benzoate, cesium benzoate, lithium benzoate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, dilithium hydrogen phosphate, disodium phenyl phosphate, disodium salts, dipotassium salts, dicesium salts, and dilithium salts of bisphenol A, and sodium salts, potassium salts, cesium salts, and lithium salts of phenol.
[0107] Examples of alkaline earth metal compounds include magnesium hydroxide, calcium hydroxide, strontium hydroxide, barium hydroxide, magnesium carbonate, calcium carbonate, strontium carbonate, barium carbonate, magnesium diacetate, calcium diacetate, strontium diacetate, and barium diacetate.
[0108] Examples of nitrogen-containing compounds include quaternary ammonium hydroxides containing alkyl or aryl groups, such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, and trimethylbenzylammonium hydroxide. Examples of bases or basic salts include tetramethylammonium borohydride, tetrabutylammonium borohydride, tetrabutyltetraphenylammonium borate, and tetraphenyltetraphenylammonium borate.
[0109] Other transesterification catalysts include salts of zinc, tin, zirconium, lead, titanium, germanium, antimony, and osmium, such as zinc acetate, zinc benzoate, zinc 2-ethylhexanoate, tin(II) chloride, tin(IV) chloride, tin(II) acetate, tin(IV) acetate, dibutyltin dilaurate, dibutyltin oxide, dibutyldimethoxytin, zirconium acetylacetonate, zirconium oxyacetate, zirconium tetrabutoxide, lead(II) acetate, lead(IV) acetate, and titanium tetrabutoxide(IV). Catalysts used in International Patent Publication No. 2011 / 010741 and Japanese Patent Application Publication No. 2017-179323 can also be used.
[0110] Furthermore, a catalyst composed of aluminum or its compounds and a phosphorus compound can be used. In this case, the concentration of the dihydroxyl component is preferably 80 μmol to 1000 μmol per mol, more preferably 90 μmol to 800 μmol, and even more preferably 100 μmol to 600 μmol per mol.
[0111] Examples of aluminum salts include organic and inorganic acid salts of aluminum. Organic acid salts of aluminum include, for example, aluminum carboxylates, specifically aluminum formate, aluminum acetate, aluminum propionate, aluminum oxalate, aluminum acrylate, aluminum laurate, aluminum stearate, aluminum benzoate, aluminum trichloroacetate, aluminum lactate, aluminum citrate, and aluminum salicylate. Inorganic acid salts of aluminum include, for example, aluminum chloride, aluminum hydroxide, aluminum chloride hydroxide, aluminum carbonate, aluminum phosphate, and aluminum phosphonate. Aluminum chelating compounds include, for example, aluminum acetylacetone, aluminum acetoacetate, aluminum ethyl acetoacetate, and aluminum diisopropoxide of ethyl acetoacetate.
[0112] Examples of phosphorus compounds include phosphonic acid compounds, hypophosphonic acid compounds, phosphonic oxide compounds, phosphonoid compounds, hypophosphonic acid compounds, and phosphonic compounds. Among these, phosphonic acid compounds, hypophosphonic acid compounds, and phosphonic oxide compounds are particularly noteworthy, especially phosphonic acid compounds.
[0113] The amount of these polymerization catalysts used relative to 1 mol of dihydroxyl content is preferably 0.1 μmol to 500 μmol, more preferably 0.5 μmol to 300 μmol, and even more preferably 1 μmol to 100 μmol.
[0114] Alternatively, a catalyst deactivator can be added in the later stages of the reaction. Known catalyst deactivators can be used effectively, with ammonium salts of sulfonic acid being preferred. Salt. Tetrabutyl dodecylbenzenesulfonate is preferred. Salts of dodecylbenzenesulfonic acid, such as tetrabutylammonium p-toluenesulfonic acid salt.
[0115] Furthermore, methyl benzenesulfonate, ethyl benzenesulfonate, butyl benzenesulfonate, octyl benzenesulfonate, phenyl benzenesulfonate, methyl p-toluenesulfonate, ethyl p-toluenesulfonate, butyl p-toluenesulfonate, octyl p-toluenesulfonate, and phenyl p-toluenesulfonate are preferred as esters of sulfonic acids. Among these, tetrabutyl dodecylbenzenesulfonate is the most preferred. Salt.
[0116] When using at least one polymerization catalyst selected from alkali metal compounds and / or alkaline earth metal compounds, the amount of these catalyst deactivators used relative to 1 mol of the catalyst is preferably 0.5 to 50 mol, more preferably 0.5 to 10 mol, and even more preferably 0.8 to 5 mol.
[0117] <Any Additives>
[0118] In the polycarbonate resin of the present invention, additives such as mold release agents, heat stabilizers (sometimes also called antioxidants), ultraviolet absorbers, bluing agents, antistatic agents, flame retardants, plasticizers, fillers, antioxidants, light stabilizers, polymeric metal passivators, lubricants, surfactants, and antibacterial agents can be appropriately added as needed to make it a resin composition. As specific mold release agents and heat stabilizers, those described in International Publication No. 2011 / 010741 are preferred examples.
[0119] As a particularly preferred release agent, glyceryl monostearate, triglyceryl stearate, pentaerythritol tetrastearate, or a mixture of triglyceryl stearate and stearyl stearate are preferably used. Furthermore, when the release agent is set to 100% by weight, the amount of the aforementioned esters in the release agent is preferably 90% by weight or more, more preferably 95% by weight or more. Additionally, relative to 100 parts by weight of polycarbonate resin, the content of the release agent is preferably in the range of 0.005 to 2.0 parts by weight, more preferably in the range of 0.01 to 0.6 parts by weight, and even more preferably in the range of 0.02 to 0.5 parts by weight.
[0120] Examples of heat stabilizers include phosphorus-based heat stabilizers, sulfur-based heat stabilizers, and hindered phenolic heat stabilizers.
[0121] In addition, examples of particularly preferred phosphorus-based heat stabilizers include tris(2,4-di-tert-butylphenyl) phosphite, bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphite, tetra(2,4-di-tert-butylphenyl)-4,4'-biphenyl diphosphite, distearate pentaerythritol diphosphite, bis(2,4-dicumylphenyl) pentaerythritol diphosphite, cyclic neopentanetetrayl bis(2,6-di-tert-butyl-4-methylphenyl) phosphite, and bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite. Furthermore, the content of the phosphorus-based heat stabilizer relative to 100 parts by weight of polycarbonate resin is preferably 0.001 to 0.2 parts by weight.
[0122] Furthermore, a particularly preferred sulfur-based heat stabilizer is pentaerythritol tetrakis(3-lauryl thiopropionate). The content of the sulfur-based heat stabilizer relative to 100 parts by weight of polycarbonate resin is preferably 0.001 to 0.2 parts by weight.
[0123] In addition, preferred hindered phenolic heat stabilizers include octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, pentaerythritol tetra[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate], 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and 1,3,5-trimethyl-2,4,6-tri( 3,5-Di-tert-butyl-4-hydroxybenzyl)benzene, N,N-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyhydrocinnamoamide), diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, 3,9-bis{1,1-dimethyl-2-[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl}-2,4,8,10-tetraoxaspiro(5,5)undecane.
[0124] The content of the hindered phenolic heat stabilizer is preferably 0.001 to 0.3 parts by weight relative to 100 parts by weight of polycarbonate resin.
[0125] Phosphorus-based heat stabilizers and hindered phenolic heat stabilizers can also be used together.
[0126] As a UV absorber, it is preferably selected from at least one UV absorber selected from benzotriazole UV absorbers, benzophenone UV absorbers, triazine UV absorbers, cyclic imino ester UV absorbers, and cyanoacrylate UV absorbers.
[0127] Among benzotriazole-based ultraviolet absorbers, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole and 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazole-2-yl)phenol] are more preferred.
[0128] Examples of benzophenone-based ultraviolet absorbers include 2-hydroxy-4-n-dodecyloxybenzophenone and 2-hydroxy-4-methoxy-2'-carboxybenzophenone.
[0129] Examples of triazine-based ultraviolet absorbers include 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[(hexyl)oxy]-phenol and 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-[(octyl)oxy]-phenol.
[0130] As a cyclic imino ester-based ultraviolet absorber, 2,2'-p-phenylenebis(3,1-benzo[a]) is particularly preferred. (Azine-4-one).
[0131] Examples of cyanoacrylate-based ultraviolet absorbers include 1,3-bis-[(2'-cyano-3',3'-diphenylacryloyl)oxy]-2,2-bis[(2-cyano-3,3-diphenylacryloyl)oxy]methyl)propane and 1,3-bis-[(2-cyano-3,3-diphenylacryloyl)oxy]benzene.
[0132] The amount of ultraviolet absorber is preferably 0.01 to 3.0 parts by weight relative to 100 parts by weight of polycarbonate resin. If it is within this range, the molded polycarbonate resin can be given sufficient weather resistance according to the application.
[0133] <Optical Components>
[0134] The optical component of the present invention comprises the aforementioned polycarbonate resin. As such an optical component, there is no particular limitation as long as the aforementioned polycarbonate resin has a useful optical application; examples include optical discs, transparent conductive substrates, optical cards, sheets, films, optical fibers, lenses, prisms, optical films, substrates, filters, hard coatings, etc.
[0135] In addition, the optical component of the present invention can be made of a resin composition comprising the above-mentioned polycarbonate resin, wherein additives such as heat stabilizers, plasticizers, light stabilizers, polymeric metal passivators, flame retardants, lubricants, antistatic agents, surfactants, antibacterial agents, ultraviolet absorbers, release agents, bluing agents, fillers, and antioxidants may be added as needed.
[0136] <Optical Lenses>
[0137] As an optical component of the present invention, an optical lens is particularly exemplified. Examples of such optical lenses include imaging lenses used in mobile phones, smartphones, tablet terminals, personal computers, digital cameras, camcorders, vehicle cameras, surveillance cameras, and sensor lenses for TOF cameras.
[0138] When manufacturing the optical lens of the present invention by injection molding, molding is preferably performed at a barrel temperature of 220–350°C and a mold temperature of 70–180°C. Molding is further preferably performed at a barrel temperature of 240–300°C and a mold temperature of 80–170°C. When the barrel temperature is above 350°C, the polycarbonate resin decomposes and colors; when the temperature is below 230°C, the melt viscosity is high, making molding difficult. Furthermore, when the mold temperature is above 180°C, it becomes difficult to remove the molded sheet made of polycarbonate resin from the mold. On the other hand, when the mold temperature is below 70°C, the resin cures too quickly within the mold during molding, making it difficult to control the shape of the molded sheet or to fully transfer the shape imparted by the mold.
[0139] The optical lens of the present invention is preferably implemented in the form of an aspherical lens as needed. An aspherical lens can achieve substantially zero spherical aberration with a single lens, thus eliminating the need to combine multiple spherical lenses to eliminate spherical aberration, enabling weight reduction and lower manufacturing costs. Therefore, aspherical lenses are particularly useful as camera lenses in optical applications.
[0140] Furthermore, the polycarbonate resin of the present invention has high molding fluidity, making it useful as a material for thin-walled, small, and complex-shaped optical lenses, particularly in imaging lenses and sensor camera lenses. Specifically, the thickness of the central portion is 0.05–3.0 mm, more preferably 0.05–2.0 mm, even more preferably 0.1–2.0 mm, and particularly preferably 0.1–1.0 mm. The diameter is 1.0 mm–20.0 mm, more preferably 1.0–10.0 mm, and even more preferably 3.0–10.0 mm. The shape is preferably a meniscus lens with one convex and one concave side.
[0141] The lens made of the polycarbonate resin of the present invention can be formed by any method such as molding, cutting, grinding, laser processing, electrical discharge machining, etching, etc. Among these methods, molding is preferred from the perspective of manufacturing cost.
[0142] Implementation Method 2
[0143] In the polycarbonate resin of the present invention, unless otherwise specified below, the matters described in Embodiment 1 above can also be applied to Embodiment 2.
[0144] <Polycarbonate resin>
[0145] The polycarbonate resin of the present invention comprises units represented by formula (1) and / or formula (2) and units represented by formula (3), preferably comprising 50 mol% or more of units represented by formula (1) and / or formula (2) in all repeating units. Preferably, it comprises 90 mol% or less of units represented by formula (1) and / or formula (2) in all repeating units, more preferably 80 mol% or less, and even more preferably 65 mol% or less. In addition, it is preferable to include more than 0% and less than 50 mol% of units represented by formula (3) in all repeating units. More preferably, it comprises 10 mol% or more of units represented by formula (3) in all repeating units, even more preferably 20 mol% or more, and particularly preferably 35 mol% or more. If it is within the above range, the Abbe number is high, and the orientation birefringence and photoelasticity are excellent, and therefore it is preferred. Furthermore, the molar ratio of the unit represented by formula (1) and / or formula (2) above to the unit represented by formula (3) above is preferably 99:1 to 50:50, more preferably 95:5 to 50:50, even more preferably 90:10 to 50:50, even more preferably 85:15 to 50:50, particularly preferably 80:20 to 50:50, and most preferably 65:35 to 50:50. If the unit represented by formula (1) and / or formula (2) and the unit represented by formula (3) are within the above range, the Abbe number is high, and the orientation birefringence and photoelastic coefficient are excellent, which is therefore preferred.
[0146]
[0147] (where R) 1 ~R 4 Each can independently represent a hydrogen atom or a hydrocarbon group with 1 to 10 carbon atoms.
[0148] The polycarbonate resin of the present invention has a weight-average molecular weight (Mw) of 10,000 or more, preferably 15,000 or more, and more preferably 20,000 or more. If the weight-average molecular weight (Mw) is 10,000 or more, it has sufficient mechanical strength as a structural material or optical material, which is preferable. Furthermore, the weight-average molecular weight (Mw) is 55,000 or less, more preferably 50,000 or less, further preferably 40,000 or less, particularly preferably less than 35,000, and most preferably 30,000 or less. If the weight-average molecular weight (Mw) is 50,000 or less, it exhibits excellent flowability during injection molding, which is therefore preferable. In particular, when the polycarbonate resin of the present invention is used in thin-walled optical components such as imaging lenses, it exhibits excellent flowability, which is therefore preferable. The weight-average molecular weight (Mw) can be determined by GPC using polystyrene, whose molecular weight is known, as a standard sample and chloroform as the developing solvent.
[0149] The absolute value of the orientation birefringence of the polycarbonate resin of the present invention is preferably 7.0 × 10⁻⁶. -3 Hereinafter, 5.0 × 10 is preferred. -3Hereinafter, 3.0 × 10 is further preferred. -3 The following is a further preferred value: 2.5 × 10⁻⁶ -3 The following is particularly preferred: 2.0 × 10 -3 The optimal value is 1.5 × 10⁻⁶. -3 Below. If the absolute value of orientation birefringence is below the above, birefringence caused by molecular orientation is less likely to occur, and therefore is preferred. Orientation birefringence is measured at a wavelength of 589 nm after cutting a 70 mm long (45 mm between fixtures) and 15 mm wide test piece from a 100 μm thick cast film made of polycarbonate resin, stretching it twice at Tg + 10 °C.
[0150] The photoelastic modulus of the polycarbonate resin of the present invention is preferably less than 25 × 10⁻⁶. -12 Pa, more preferably 20 × 10 Pa - 12 Pa or less. If the photoelasticity coefficient is within the above range, stress-induced birefringence is less likely to occur, and therefore it is preferred. The photoelasticity coefficient was measured using a Spectroellipsometer M-220 manufactured by Nippon Spectrophotometer Co., Ltd., on a test piece cut from a 100 μm thick cast film of polycarbonate resin with a length of 50 mm and a width of 10 mm.
[0151] The polycarbonate resin of the present invention has a refractive index nd, measured at a temperature of 20°C and a wavelength of 587.56 nm, preferably 1.540 or higher, more preferably 1.550 or higher, even more preferably 1.560 or higher, even more preferably 1.570 or higher, and particularly preferably 1.575 or higher. If the refractive index is above the above range, the optical components can be thinned, which is therefore preferred. Furthermore, the refractive index nd can be 1.610 or lower, 1.600 or lower, 1.590 or lower, or 1.580 or lower. If the refractive index nd is within the above range, the degree of freedom in optical design is increased when using multiple lenses in combination, which is therefore preferred.
[0152] The Abbe number of the polycarbonate resin of the present invention is preferably 25.0 or higher, more preferably 28.0 or higher, even more preferably 31.0 or higher, even more preferably 34.0 or higher, and particularly preferably 36.0 or higher. If the Abbe number is above the above-mentioned values, the chromatic aberration of the optical component is reduced, which is therefore preferred. Alternatively, the Abbe number can be 57.0 or lower, 55.0 or lower, 50.0 or lower, or 45.0 or lower. If the Abbe number is within the above range, the degree of freedom in optical design is increased when using multiple lenses in combination, which is therefore preferred.
[0153] Here, the Abbe number (νd) is calculated from the refractive index at temperatures of 20°C and wavelengths of 486.13 nm, 587.56 nm, and 656.27 nm using the following formula.
[0154] νd=(nd-1) / (nF-nC)
[0155] nd refers to the refractive index at a wavelength of 587.56 nm.
[0156] nF refers to the refractive index at a wavelength of 486.13 nm.
[0157] nC refers to the refractive index at a wavelength of 656.27 nm.
[0158] The glass transition temperature of the polycarbonate resin of the present invention is preferably 130°C or higher, more preferably 133°C or higher, and even more preferably 136°C or higher. If the glass transition temperature is within the above range, the usable temperature range of the optical component becomes higher, which is therefore preferred. Alternatively, the glass transition temperature can be 155°C or lower, 150°C or lower, 145°C or lower, or 140°C or lower. If the glass transition temperature is within the above range, the balance between heat resistance and moldability is excellent, which is therefore preferred.
[0159] The thermal decomposition temperature of the polycarbonate resin of the present invention is preferably 370°C or higher, more preferably 375°C or higher. If the thermal decomposition temperature is above this value, the polycarbonate resin of the present invention exhibits excellent processing stability during molding and less coloring, and is therefore preferred. Alternatively, the thermal decomposition temperature can be 420°C or lower, or 400°C or lower. The thermal decomposition temperature can be determined by TGA (thermogravimetric analysis), and is the temperature at which a 5% weight reduction occurs.
[0160] The melt viscosity (Pa·s) of the polycarbonate resin of the present invention at 260°C and a shear rate of 1216 / sec is preferably 30 or more, more preferably 50 or more, and even more preferably 70 or more. The melt viscosity (Pa·s) at 260°C and a shear rate of 1216 / sec is preferably 500 or less, more preferably 400 or less, even more preferably 300 or less, and particularly preferably 200 or less. If the melt viscosity is within the above range, the moldability during injection molding is excellent, and therefore preferred. Especially when injection molding thin-walled articles such as lenses, the melt viscosity during molding is very important; if the melt viscosity is within the above range, the desired lens shape can be obtained, and therefore preferred. The melt viscosity was measured using a Capilograph 1D manufactured by Toyo Seiki Co., Ltd. after drying the polycarbonate resin at 120°C for 4 hours.
[0161] The specific viscosity of the polycarbonate resin of the present invention is preferably 0.12 to 0.32, more preferably 0.18 to 0.30. If the specific viscosity is 0.12 to 0.32, the balance between moldability and strength is excellent.
[0162] The specific viscosity is determined by measuring the specific viscosity (ηSP) of a solution obtained by dissolving 0.7g of polycarbonate resin in 100ml of dichloromethane at 20°C using an Ostwald viscometer, and is calculated by the following formula.
[0163] ηSP = (t - t0) / t0
[0164] [t0 is the number of seconds for the dichloromethane to fall, and t is the number of seconds for the sample solution to fall.]
[0165] Implementation Method 3
[0166] In the polycarbonate resin of the present invention, unless otherwise specified below, the matters described in Embodiment 1 above can also be applied to Embodiment 3.
[0167] <Polycarbonate resin>
[0168] The polycarbonate resin of the present invention comprises units represented by formula (1) and / or formula (2) and units represented by formula (3), preferably comprising more than 0% and less than 50 mol% of units represented by formula (1) and / or formula (2) in all repeating units. Preferably, it comprises more than 10 mol% of units represented by formula (1) and / or formula (2) in all repeating units, more preferably more than 20 mol%, and even more preferably more than 35 mol% and less than 50 mol%. In addition, it is preferable to comprise more than 50 mol% of units represented by formula (3) in all repeating units. Preferably, it comprises less than 90 mol% of units represented by formula (3) in all repeating units, more preferably less than 80 mol%, and even more preferably less than 65 mol%. If it is within the above range, the orientation birefringence is small, the refractive index and the glass transition temperature are high, and therefore it is preferred. Furthermore, the molar ratio of the unit represented by formula (1) and / or formula (2) above to the unit represented by formula (3) above is preferably 1:99 to 49:51, more preferably 5:95 to 49:51, even more preferably 10:90 to 49:51, even more preferably 15:85 to 49:51, particularly preferably 20:80 to 49:51, and most preferably 35:65 to 49:51. If the unit represented by formula (1) and / or formula (2) and the unit represented by formula (3) are within the above range, the orientation birefringence is small, the refractive index and the glass transition temperature are high, and therefore it is preferred.
[0169]
[0170] (where R) 1 ~R 4Each can independently represent a hydrogen atom or a hydrocarbon group with 1 to 10 carbon atoms.
[0171] The polycarbonate resin of the present invention has a weight-average molecular weight (Mw) of 10,000 or more, preferably 15,000 or more, and more preferably 20,000 or more. If the weight-average molecular weight (Mw) is 10,000 or more, it has sufficient mechanical strength as a structural material or optical material, which is preferable. Furthermore, the weight-average molecular weight (Mw) is 55,000 or less, more preferably 50,000 or less, further preferably 40,000 or less, particularly preferably less than 35,000, and most preferably 30,000 or less. If the weight-average molecular weight (Mw) is 50,000 or less, it exhibits excellent flowability during injection molding, which is therefore preferable. In particular, when the polycarbonate resin of the present invention is used in thin-walled optical components such as imaging lenses, it exhibits excellent flowability, which is therefore preferable. The weight-average molecular weight (Mw) can be determined by GPC using polystyrene, whose molecular weight is known, as a standard sample and chloroform as the developing solvent.
[0172] The absolute value of the orientation birefringence of the polycarbonate resin of the present invention is preferably 3.0 × 10⁻⁶. -3 Hereinafter, 2.0 × 10 is preferred. -3 Hereinafter, 1.0 × 10 is further preferred. -3 The following is a further preferred value: 0.5 × 10⁻⁶ -3 Below. If the absolute value of orientation birefringence is below the above, birefringence caused by molecular orientation is less likely to occur, and therefore is preferred. Orientation birefringence is measured at a wavelength of 589 nm after cutting a 70 mm long (45 mm between fixtures) and 15 mm wide test piece from a 100 μm thick cast film made of polycarbonate resin, stretching it twice at Tg + 10 °C.
[0173] The photoelastic modulus of the polycarbonate resin of the present invention is preferably less than 35 × 10⁻⁶. -12 Pa, more preferably 30 × 10 Pa - 12 Pa or less, more preferably 25 × 10 Pa -12 Pa or less. If the photoelasticity coefficient is within the above range, stress-induced birefringence is less likely to occur, and therefore it is preferred. The photoelasticity coefficient was measured using a Spectroellipsometer M-220 manufactured by Nippon Spectrophotometer Co., Ltd., on a test piece cut from a 100 μm thick cast film of polycarbonate resin with a length of 50 mm and a width of 10 mm.
[0174] The refractive index nd of the polycarbonate resin of the present invention, measured at a temperature of 20°C and a wavelength of 587.56 nm, is preferably 1.600 or higher, more preferably 1.605 or higher, even more preferably 1.610 or higher, even more preferably 1.615 or higher, and particularly preferably 1.620 or higher. If the refractive index is above the above range, the optical components can be thinned, which is therefore preferred. Furthermore, the refractive index nd can be 1.650 or lower, 1.645 or lower, 1.640 or lower, or 1.635 or lower. If the refractive index nd is within the above range, the degree of freedom in optical design is increased when using multiple lenses in combination, which is therefore preferred.
[0175] The Abbe number of the polycarbonate resin of the present invention is preferably 25.0 or higher, more preferably 30.0 or higher. If the Abbe number is above or higher, the chromatic aberration of the optical component is reduced, which is therefore preferred. Alternatively, the Abbe number can be 33.0 or lower, or 32.0 or lower. If the Abbe number is within the above range, the degree of freedom in optical design is increased when using multiple lenses in combination, which is therefore preferred.
[0176] Here, the Abbe number (νd) is calculated from the refractive index at temperatures of 20°C and wavelengths of 486.13 nm, 587.56 nm, and 656.27 nm using the following formula.
[0177] νd=(nd-1) / (nF-nC)
[0178] nd refers to the refractive index at a wavelength of 587.56 nm.
[0179] nF refers to the refractive index at a wavelength of 486.13 nm.
[0180] nC refers to the refractive index at a wavelength of 656.27 nm.
[0181] The glass transition temperature of the polycarbonate resin of the present invention is preferably 138°C or higher, more preferably 140°C or higher, even more preferably 142°C or higher, and even more preferably 144°C or higher. If the glass transition temperature is within the above range, the usable temperature range of the optical component becomes higher, which is therefore preferred. Alternatively, the glass transition temperature can be 160°C or lower, 155°C or lower, or 150°C or lower. If the glass transition temperature is within the above range, the balance between heat resistance and moldability is excellent, which is therefore preferred.
[0182] The thermal decomposition temperature of the polycarbonate resin of the present invention is preferably 370°C or higher, more preferably 375°C or higher, and even more preferably 380°C or higher. If the thermal decomposition temperature is above the above, the polycarbonate resin of the present invention exhibits excellent processing stability during molding and less coloring, and is therefore preferred. Alternatively, the thermal decomposition temperature can be 420°C or lower, or 400°C or lower. The thermal decomposition temperature can be determined by TGA (thermogravimetric analysis), and is the temperature at which a 5% weight reduction occurs.
[0183] The melt viscosity (Pa·s) of the polycarbonate resin of the present invention at 260°C and a shear rate of 1216 / sec is preferably 30 or more, more preferably 50 or more, and even more preferably 70 or more. The melt viscosity (Pa·s) at 260°C and a shear rate of 1216 / sec is preferably 500 or less, more preferably 400 or less, even more preferably 300 or less, and particularly preferably 200 or less. If the melt viscosity is within the above range, the moldability during injection molding is excellent, and therefore preferred. Especially when injection molding thin-walled articles such as lenses, the melt viscosity during molding is very important; if the melt viscosity is within the above range, the desired lens shape can be obtained, and therefore preferred. The melt viscosity was measured using a Capilograph 1D manufactured by Toyo Seiki Co., Ltd. after drying the polycarbonate resin at 120°C for 4 hours.
[0184] The specific viscosity of the polycarbonate resin of the present invention is preferably 0.12 to 0.32, more preferably 0.18 to 0.30. If the specific viscosity is 0.12 to 0.32, the balance between moldability and strength is excellent.
[0185] The specific viscosity is determined by measuring the specific viscosity (ηSP) of a solution obtained by dissolving 0.7g of polycarbonate resin in 100ml of dichloromethane at 20°C using an Ostwald viscometer, and is calculated by the following formula.
[0186] ηSP = (t - t0) / t0
[0187] [t0 is the number of seconds for the dichloromethane to fall, and t is the number of seconds for the sample solution to fall.]
[0188] The present invention is further illustrated by the following embodiments, but the present invention is not limited thereto.
[0189] Example
[0190] The following methods will be used for evaluation.
[0191] <Copolymer ratio of polycarbonate resin>
[0192] Determined by using JEOL-prepared JNM-ECZ400S 1 The copolymerization ratio of each polycarbonate resin was calculated using H NMR.
[0193] <Weight-average molecular weight (Mw)>
[0194] The weight-average molecular weight (Mw) was determined using an EcoSEC HLC-8320 GPC prepared by TOSOH under the conditions described below.
[0195] Detector: UV-8420, Solvent: Chloroform, Column: TOSOH TSKgel Supermultipore HZM-M×3 + TSKgel guard column (4.6×200nm), Measurement temperature: 40℃, Flow rate: 0.35ml / min, Injection volume: 5μl, Sample concentration: 1mg / 5ml, Standard sample: TSKstandard Polystyrene
[0196] <Refractive Index>
[0197] After preparing and grinding 3mm thick test pieces of each polycarbonate resin, the refractive index nd (587.56nm) was measured using a Shimadzu Kalnew precision refractometer KPR-2000.
[0198] <Abbe Numbers>
[0199] The Abbe number (νd) is calculated from the refractive index at temperatures of 20°C and wavelengths of 486.13 nm, 587.56 nm, and 656.27 nm using the following formula.
[0200] νd=(nd-1) / (nF-nC)
[0201] nd refers to the refractive index at a wavelength of 587.56 nm.
[0202] nF refers to the refractive index at a wavelength of 486.13 nm.
[0203] nC refers to the refractive index at a wavelength of 656.27 nm.
[0204] <Absolute value of orientation birefringence (|Δn|)>
[0205] Polycarbonate resin was dissolved in dichloromethane, cast onto a glass dish, and thoroughly dried to produce a 100 μm thick cast film. Test pieces with a length of 70 mm (45 mm between fixtures) and a width of 15 mm were cut from this film and stretched twice at Tg +10℃. The phase difference (Re) at 589 nm was measured using an M-220 ellipsometer manufactured by Nippon Spectrophotometer Co., Ltd. The absolute value of the orientation birefringence (|Δn|) was calculated using the following formula.
[0206] |Δn| = |Re / d|
[0207] Δn: Orientation birefringence
[0208] Re: Phase difference (nm)
[0209] d: Thickness (nm)
[0210] <Photoelastic coefficient>
[0211] Polycarbonate resin was dissolved in dichloromethane, cast onto a glass dish, and thoroughly dried to produce a 100 μm thick cast film. Test pieces with a length of 50 mm and a width of 10 mm were cut from this film, and the photoelasticity coefficient was measured using an M-220 ellipsometry manufactured by Nippon Spectrophotometer Co., Ltd.
[0212] <Glass transition temperature (Tg)>
[0213] The obtained polycarbonate resin was analyzed using a Discovery DSC 25Auto instrument manufactured by TA Instruments at a heating rate of 20 °C / min. Samples were analyzed in the range of 5–10 mg.
[0214] <Thermal decomposition temperature (Td-5)>
[0215] The obtained polycarbonate resin was tested using a TA Instruments SDT650 thermometer at a heating rate of 20°C / min. The temperature at which the weight decreased by 5% based on the weight at 50°C was determined. Samples were tested in doses of 3–4 mg.
[0216] <Melt viscosity (Pa·s)>
[0217] After drying the polycarbonate resin at 120°C for 4 hours, the melt viscosity at 260°C and a shear rate of 1216 / sec was measured using a Capilograph 1D manufactured by Toyo Seiki Co., Ltd.
[0218] <Example 1>
[0219] 87.70 g (0.20 mol) of 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene (hereinafter sometimes abbreviated as BPEF), 52.48 g (0.20 mol) of pentacyclopentadecanedimethanol (hereinafter sometimes abbreviated as PCPDM), 89.12 g (0.42 mol) of diphenyl carbonate, and 17 μL of a 60 mmol / L sodium bicarbonate aqueous solution (2.5 μmol sodium bicarbonate) and 227 μL of a 274 mmol / L tetramethylammonium hydroxide aqueous solution (15 μmol tetramethylammonium hydroxide) as catalysts were heated to 180 °C under a nitrogen atmosphere to melt them. Then, while reducing the pressure inside the reactor to 20 kPa over 40 minutes, the temperature was increased to 250 °C at a rate of 60 °C / hr. After 70% of the theoretical amount of phenol distilled off, the pressure inside the reactor was reduced to below 133 Pa over 1 hour. The reaction was then stopped by stirring at 260°C for 40 minutes under a pressure below 133 Pa in the reactor, and the resin was removed. The copolymerization ratio of the obtained polycarbonate resin from BPEF and PCPDM was determined by 1H NMR. The weight-average molecular weight (Mw), refractive index, Abbe number, glass transition temperature, thermal decomposition temperature, absolute value of orientation birefringence, photoelastic coefficient, and melt viscosity of the polycarbonate resin were evaluated. Then, the obtained resin was dried at 120°C for 4 hours, and based on the weight of the resin, 0.05% by weight of bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphite and 0.10% by weight of glyceryl monostearate were added, and granulation was carried out using a φ15mm twin-screw extruder with venting. After drying the particles at 120℃ for 4 hours, a lens with a thickness of 0.3mm, a convex surface curvature radius of 5mm, a concave surface curvature radius of 4mm, and a diameter of φ5mm was obtained by injection molding at a barrel temperature of 260℃ and a mold temperature of Tg-5℃ of polycarbonate resin.
[0220] <Example 2>
[0221] The polycarbonate resin was prepared in the same manner as in Example 1, with 52.62 g (0.12 mol) of BPEF and 73.47 g (0.28 mol) of PCPDM. The copolymerization ratio of BPEF and PCPDM in the obtained polycarbonate resin was determined by 1H NMR. The weight-average molecular weight Mw, refractive index, Abbe number, glass transition temperature, thermal decomposition temperature, absolute value of orientation birefringence, photoelastic coefficient, and melt viscosity of the polycarbonate resin were evaluated. Then, a lens with a thickness of 0.3 mm, a convex radius of curvature of 5 mm, a concave radius of curvature of 4 mm, and a φ of 5 mm was obtained by injection molding in the same manner as in Example 1.
[0222] <Example 3>
[0223] The polycarbonate resin was prepared in the same manner as in Example 1, with 43.85 g (0.10 mol) of BPEF and 78.72 g (0.30 mol) of PCPDM. The copolymerization ratio of BPEF and PCPDM in the obtained polycarbonate resin was determined by 1H NMR. The weight-average molecular weight Mw, refractive index, Abbe number, glass transition temperature, thermal decomposition temperature, absolute value of orientation birefringence, photoelastic coefficient, and melt viscosity of the polycarbonate resin were evaluated. Then, a lens with a thickness of 0.3 mm, a convex radius of curvature of 5 mm, a concave radius of curvature of 4 mm, and a φ of 5 mm was obtained by injection molding in the same manner as in Example 1.
[0224] <Example 4>
[0225] The polycarbonate resin was prepared in the same manner as in Example 1, with 8.78 g (0.02 mol) of BPEF and 99.71 g (0.38 mol) of PCPDM. The copolymerization ratio of BPEF and PCPDM in the obtained polycarbonate resin was determined by 1H NMR. The weight-average molecular weight Mw, refractive index, Abbe number, glass transition temperature, thermal decomposition temperature, absolute value of orientation birefringence, photoelastic coefficient, and melt viscosity of the polycarbonate resin were evaluated. Then, a lens with a thickness of 0.3 mm, a convex radius of curvature of 5 mm, a concave radius of curvature of 4 mm, and a φ of 5 mm was obtained by injection molding in the same manner as in Example 1.
[0226] <Comparative Example 1>
[0227] 45.66 g (0.20 mol) of bisphenol A (hereinafter sometimes referred to as BPA), 52.48 g (0.20 mol) of PCPDM, 86.97 g (0.406 mol) of diphenyl carbonate, and 1.09 mg (12 μmol) of sodium bicarbonate as a catalyst were heated to 180 °C under a nitrogen atmosphere to melt them. Then, the reactor pressure was increased to 20 kPa (150 mmHg), and the temperature was raised to 200 °C at a rate of 60 °C / hr, and maintained at this temperature for 40 minutes. Next, the temperature was increased to 225 °C at a rate of 75 °C / hr, and after 40 minutes of this increase, the reactor pressure was maintained at this temperature for 1 hour to bring it below 133 Pa (1 mmHg). Finally, the temperature was increased to 235 °C at a rate of 105 °C / hr, and the reaction was carried out for a total of 6 hours with stirring. After the reaction was completed, nitrogen was blown into the reactor to restore atmospheric pressure, and the resulting resin was removed. The copolymerization ratio of BPA and PCPDM in the obtained polycarbonate resin was determined by 1H NMR. The weight-average molecular weight (Mw), refractive index, Abbe number, glass transition temperature, thermal decomposition temperature, absolute value of oriented birefringence, photoelastic coefficient, and melt viscosity of the polycarbonate resin were evaluated. Then, an attempt was made to injection mold a lens with a thickness of 0.3 mm, a convex radius of curvature of 5 mm, a concave radius of curvature of 4 mm, and a diameter of 5 mm, using the same method as in Example 1. However, due to the high melt viscosity of the resin, it was impossible to mold a thin-walled lens of this shape.
[0228] <Comparative Example 2>
[0229] The polycarbonate resin was prepared using the same method as in Comparative Example 1, with 63.92 g (0.28 mol) of BPA and 31.49 g (0.12 mol) of PCPDM. The copolymerization ratio of BPA and PCPDM in the obtained polycarbonate resin was determined by 1H NMR. The weight-average molecular weight Mw, refractive index, Abbe number, glass transition temperature, thermal decomposition temperature, absolute value of orientation birefringence, photoelastic coefficient, and melt viscosity of the polycarbonate resin were evaluated. Then, an attempt was made to injection mold a lens with a thickness of 0.3 mm, a convex radius of curvature of 5 mm, a concave radius of curvature of 4 mm, and a diameter of 5 mm, using the same method as in Example 1. However, due to the high melt viscosity of the resin, it was impossible to mold a thin-walled lens of this shape.
[0230] <Comparative Example 3>
[0231] The polycarbonate resin was prepared in the same manner as in Comparative Example 1, with 27.40 g (0.12 mol) of BPA and 73.47 g (0.28 mol) of PCPDM. The copolymerization ratio of BPA and PCPDM in the obtained polycarbonate resin was determined by 1H NMR. The weight-average molecular weight Mw, refractive index, Abbe number, glass transition temperature, thermal decomposition temperature, absolute value of oriented birefringence, photoelastic coefficient, and melt viscosity of the polycarbonate resin were evaluated. Then, an attempt was made to injection mold a lens with a thickness of 0.3 mm, a convex radius of curvature of 5 mm, a concave radius of curvature of 4 mm, and a diameter of 5 mm, using the same method as in Example 1. However, due to the high melt viscosity of the resin, it was not possible to mold a thin-walled lens of this shape.
[0232] <Comparative Example 4>
[0233] 87.70 g (0.20 mol) of BPEF, 52.48 g (0.20 mol) of PCPDM, 87.40 g (0.41 mol) of diphenyl carbonate, and 17 μL of a 60 mmol / L sodium bicarbonate aqueous solution (2.5 μmol sodium bicarbonate) and 227 μL of a 274 mmol / L tetramethylammonium hydroxide aqueous solution (15 μmol tetramethylammonium hydroxide) as catalysts were heated to 180 °C under a nitrogen atmosphere to melt them. Then, while reducing the reactor pressure to 20 kPa over 40 minutes, the temperature was increased to 250 °C at a rate of 60 °C / hr. After 70% of the theoretical amount of phenol distilled off, the reactor pressure was reduced to below 133 Pa over 1 hour. The reaction was then stopped by stirring at 260 °C for 40 minutes at a reactor pressure below 133 Pa, and the resin was removed. The copolymerization ratio of the obtained polycarbonate resin from BPEF and PCPDM was determined by 1H NMR. The weight-average molecular weight (Mw), refractive index, Abbe number, glass transition temperature, thermal decomposition temperature, absolute value of oriented birefringence, photoelastic coefficient, and melt viscosity of the polycarbonate resin were evaluated. Then, an attempt was made to injection mold a lens with a thickness of 0.3 mm, a convex radius of curvature of 5 mm, a concave radius of curvature of 4 mm, and a diameter of 5 mm, using the same method as in Example 1. However, due to the high melt viscosity of the resin, it was impossible to mold a thin-walled lens of this shape.
[0234] <Comparative Example 5>
[0235] The polycarbonate resin was prepared using 70.16 g (0.16 mol) of BPEF and 62.97 g (0.24 mol) of PCPDM, otherwise in the same manner as Comparative Example 4. The copolymerization ratio of BPEF and PCPDM in the obtained polycarbonate resin was determined by 1H NMR. The weight-average molecular weight Mw, refractive index, Abbe number, glass transition temperature, thermal decomposition temperature, absolute value of oriented birefringence, photoelastic coefficient, and melt viscosity of the polycarbonate resin were evaluated. Then, an attempt was made to injection mold a lens with a thickness of 0.3 mm, a convex radius of curvature of 5 mm, a concave radius of curvature of 4 mm, and a diameter of 5 mm, using the same method as in Example 1. However, due to the high melt viscosity of the resin, it was impossible to mold a thin-walled lens of this shape.
[0236] <Comparative Example 6>
[0237] The amount of BPEF added was 52.62 g (0.12 mol), and the amount of PCPDM added was 73.47 g (0.28 mol). Otherwise, the polycarbonate resin was prepared in the same manner as in Comparative Example 4. The copolymerization ratio of BPEF and PCPDM in the obtained polycarbonate resin was determined by 1H NMR. The weight-average molecular weight Mw, refractive index, Abbe number, glass transition temperature, thermal decomposition temperature, absolute value of oriented birefringence, photoelastic coefficient, and melt viscosity of the polycarbonate resin were evaluated. Then, an attempt was made to injection mold a lens with a thickness of 0.3 mm, a convex radius of curvature of 5 mm, a concave radius of curvature of 4 mm, and a diameter of 5 mm, using the same method as in Example 1. However, due to the high melt viscosity of the resin, it was impossible to mold a thin-walled lens of this shape.
[0238]
[0239] Compared to the comparative examples, Examples 1-4 of the present invention exhibit lower melt viscosity, resulting in superior formability during injection molding. Furthermore, they demonstrate excellent orientational birefringence, thus minimizing birefringence caused by molecular orientation when optical components are obtained through injection molding or the like. Additionally, they have a low photoelasticity coefficient, further reducing stress-induced birefringence when optical components are obtained through injection molding or the like. Therefore, the birefringence of the optical component is reduced, which is preferable.
[0240] <Example 5>
[0241] 166.64 g (0.38 mol) of 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene (hereinafter sometimes abbreviated as BPEF), 5.25 g (0.02 mol) of pentacyclopentadecanedimethanol (hereinafter sometimes abbreviated as PCPDM), 89.12 g (0.42 mol) of diphenyl carbonate, and 17 μL of a 60 mmol / L sodium bicarbonate aqueous solution (2.5 μmol sodium bicarbonate) and 227 μL of a 274 mmol / L tetramethylammonium hydroxide aqueous solution (15 μmol tetramethylammonium hydroxide) as catalysts were heated to 180 °C under a nitrogen atmosphere to melt them. Then, while reducing the pressure inside the reactor to 20 kPa over 40 minutes, the temperature was increased to 250 °C at a rate of 60 °C / hr. After 70% of the theoretical amount of phenol distilled off, the pressure inside the reactor was reduced to below 133 Pa over 1 hour. The reaction was then stopped by stirring at 260°C and a pressure below 133 Pa in the reactor for 40 minutes, and the resin was removed. The copolymerization ratio of the obtained polycarbonate resin from BPEF and PCPDM was determined by 1H NMR. The weight-average molecular weight (Mw), refractive index, Abbe number, glass transition temperature, thermal decomposition temperature, absolute value of orientation birefringence, photoelastic coefficient, and melt viscosity of the polycarbonate resin were evaluated. Then, using the same method as in Example 1, a lens with a thickness of 0.3 mm, a convex radius of curvature of 5 mm, a concave radius of curvature of 4 mm, and a diameter of 5 mm was obtained by injection molding.
[0242] <Example 6>
[0243] The polycarbonate resin was prepared in the same manner as in Example 1, with 131.56 g (0.30 mol) of BPEF and 26.24 g (0.10 mol) of PCPDM. The copolymerization ratio of BPEF and PCPDM in the obtained polycarbonate resin was determined by 1H NMR. The weight-average molecular weight Mw, refractive index, Abbe number, glass transition temperature, thermal decomposition temperature, absolute value of orientation birefringence, photoelastic coefficient, and melt viscosity of the polycarbonate resin were evaluated. Then, a lens with a thickness of 0.3 mm, a convex radius of curvature of 5 mm, a concave radius of curvature of 4 mm, and a φ of 5 mm was obtained by injection molding in the same manner as in Example 1.
[0244] <Example 7>
[0245] The polycarbonate resin was prepared in the same manner as in Example 1, with 96.47 g (0.22 mol) of BPEF and 47.23 g (0.18 mol) of PCPDM. The copolymerization ratio of BPEF and PCPDM in the obtained polycarbonate resin was determined by 1H NMR. The weight-average molecular weight Mw, refractive index, Abbe number, glass transition temperature, thermal decomposition temperature, absolute value of orientation birefringence, photoelastic coefficient, and melt viscosity of the polycarbonate resin were evaluated. Then, a lens with a thickness of 0.3 mm, a convex radius of curvature of 5 mm, a concave radius of curvature of 4 mm, and a φ of 5 mm was obtained by injection molding using the same method as in Example 1.
[0246] <Comparative Example 7>
[0247] 45.66 g (0.20 mol) of bisphenol A (hereinafter sometimes referred to as BPA), 52.48 g (0.20 mol) of PCPDM, 86.97 g (0.406 mol) of diphenyl carbonate, and 1.09 mg (12 μmol) of sodium bicarbonate as a catalyst were heated to 180 °C under a nitrogen atmosphere to melt them. Then, the reactor pressure was increased to 20 kPa (150 mmHg), and the temperature was raised to 200 °C at a rate of 60 °C / hr, and maintained at this temperature for 40 minutes. Next, the temperature was increased to 225 °C at a rate of 75 °C / hr, and after 40 minutes of this increase, the reactor pressure was maintained at this temperature for 1 hour to bring it below 133 Pa (1 mmHg). Finally, the temperature was increased to 235 °C at a rate of 105 °C / hr, and the reaction was carried out for a total of 6 hours with stirring. After the reaction was completed, nitrogen was blown into the reactor to restore atmospheric pressure, and the resulting resin was removed. The copolymerization ratio of BPA and PCPDM in the obtained polycarbonate resin was determined by 1H NMR. The weight-average molecular weight (Mw), refractive index, Abbe number, glass transition temperature, thermal decomposition temperature, absolute value of oriented birefringence, photoelastic coefficient, and melt viscosity of the polycarbonate resin were evaluated. Then, an attempt was made to injection mold a lens with a thickness of 0.3 mm, a convex radius of curvature of 5 mm, a concave radius of curvature of 4 mm, and a diameter of 5 mm, using the same method as in Example 1. However, due to the high melt viscosity of the resin, it was impossible to mold a thin-walled lens of this shape.
[0248] <Comparative Example 8>
[0249] The polycarbonate resin was prepared using the same method as in Comparative Example 1, with 63.92 g (0.28 mol) of BPA and 31.49 g (0.12 mol) of PCPDM. The copolymerization ratio of BPA and PCPDM in the obtained polycarbonate resin was determined by 1H NMR. The weight-average molecular weight Mw, refractive index, Abbe number, glass transition temperature, thermal decomposition temperature, absolute value of orientation birefringence, photoelastic coefficient, and melt viscosity of the polycarbonate resin were evaluated. Then, an attempt was made to injection mold a lens with a thickness of 0.3 mm, a convex radius of curvature of 5 mm, a concave radius of curvature of 4 mm, and a diameter of 5 mm, using the same method as in Example 1. However, due to the high melt viscosity of the resin, it was impossible to mold a thin-walled lens of this shape.
[0250] <Comparative Example 9>
[0251] The polycarbonate resin was prepared in the same manner as in Comparative Example 1, with 27.40 g (0.12 mol) of BPA and 73.47 g (0.28 mol) of PCPDM. The copolymerization ratio of BPA and PCPDM in the obtained polycarbonate resin was determined by 1H NMR. The weight-average molecular weight Mw, refractive index, Abbe number, glass transition temperature, thermal decomposition temperature, absolute value of oriented birefringence, photoelastic coefficient, and melt viscosity of the polycarbonate resin were evaluated. Then, an attempt was made to injection mold a lens with a thickness of 0.3 mm, a convex radius of curvature of 5 mm, a concave radius of curvature of 4 mm, and a diameter of 5 mm, using the same method as in Example 1. However, due to the high melt viscosity of the resin, it was not possible to mold a thin-walled lens of this shape.
[0252] <Comparative Example 10>
[0253] The amount of BPEF added was 122.79 g (0.28 mol), and the amount of PCPDM added was 31.49 g (0.12 mol). Otherwise, the polycarbonate resin was prepared in the same manner as in Comparative Example 4. The copolymerization ratio of BPEF and PCPDM in the obtained polycarbonate resin was determined by 1H NMR. The weight-average molecular weight Mw, refractive index, Abbe number, glass transition temperature, thermal decomposition temperature, absolute value of oriented birefringence, photoelastic coefficient, and melt viscosity of the polycarbonate resin were evaluated. Then, an attempt was made to injection mold a lens with a thickness of 0.3 mm, a convex radius of curvature of 5 mm, a concave radius of curvature of 4 mm, and a diameter of 5 mm, using the same method as in Example 1. However, due to the high melt viscosity of the resin, it was impossible to mold a thin-walled lens of this shape.
[0254]
[0255] Compared to the comparative examples, Examples 5-7 of the present invention exhibit low melt viscosity, resulting in excellent formability during injection molding. Furthermore, they demonstrate excellent orientational birefringence, thus minimizing birefringence caused by molecular orientation when obtaining optical components via injection molding or the like. Additionally, they possess high refractive index and glass transition temperature, making them preferred as optical components.
[0256] Industrial availability
[0257] The polycarbonate resin of the present invention is used in optical materials and can be used in optical components such as lenses, prisms, optical discs, transparent conductive substrates, optical cards, sheets, films, optical fibers, optical films, filters, and hard coatings. It is particularly useful in imaging lenses or sensor camera lenses, and is extremely useful in imaging lenses.
Claims
1. A polycarbonate resin comprising units represented by formula (1) and / or formula (2) and units represented by formula (3), having a weight-average molecular weight Mw of 10,000 to 55,000. In the formula, R 1 ~R 4 Each can independently represent a hydrocarbon group with 1 to 10 hydrogen or carbon atoms.
2. The polycarbonate resin according to claim 1, wherein, R in equation (3) 1 ~R 4 It is a hydrogen atom.
3. The polycarbonate resin according to claim 1 or 2, wherein, The molar ratio of the unit represented by formula (1) and / or formula (2) to the unit represented by formula (3) is 99:1 to 1:
99.
4. The polycarbonate resin according to claim 3, wherein, The molar ratio of the unit represented by formula (1) and / or formula (2) to the unit represented by formula (3) is 65:35 to 35:
65.
5. The polycarbonate resin according to claim 1 or 2, wherein, The absolute value of oriented birefringence is 7.0 × 10⁻⁶. -3 the following.
6. The polycarbonate resin according to claim 1 or 2, wherein, The photoelastic modulus is less than 35×10 -12 Pa.
7. The polycarbonate resin according to claim 1, wherein, The total repeating units contain more than 50 mol% of units represented by formula (1) and / or formula (2), with a weight-average molecular weight Mw of 10,000 to 50,000.
8. The polycarbonate resin according to claim 7, wherein, The entire repeating unit contains more than 0% and less than 50 mol% of the unit represented by equation (3).
9. The polycarbonate resin according to claim 7 or 8, wherein, The molar ratio of the unit represented by formula (1) and / or formula (2) to the unit represented by formula (3) is 99:1 to 50:
50.
10. The polycarbonate resin according to claim 7 or 8, wherein, The photoelastic modulus is less than 25 × 10 -12 Pa.
11. The polycarbonate resin according to claim 7 or 8, wherein, An Abbe number of 25.0 or higher.
12. The polycarbonate resin according to claim 1, wherein, The entire repeating unit contains more than 0% and less than 50 mol% of the units represented by formula (1) and / or formula (2), with a weight-average molecular weight Mw of 10,000 to 50,000.
13. The polycarbonate resin according to claim 12, wherein, The entire repeating unit contains more than 50 mol% of the unit represented by equation (3).
14. The polycarbonate resin according to claim 12 or 13, wherein, The molar ratio of the unit represented by formula (1) and / or formula (2) to the unit represented by formula (3) is 1:99 to 49:
51.
15. The polycarbonate resin according to claim 12 or 13, wherein, The absolute value of oriented birefringence is 3.0 × 10⁻⁶. -3 the following.
16. The polycarbonate resin according to claim 12 or 13, wherein, The refractive index nd is above 1.
600.
17. The polycarbonate resin according to claim 12 or 13, wherein, The glass transition temperature is above 140℃.
18. An optical component comprising the polycarbonate resin of any one of claims 1, 2, 7 or 12.
19. The optical component according to claim 18, wherein, The optical component is an imaging lens or a sensor camera lens.
20. The imaging lens or sensing camera lens according to claim 19, wherein, The thickness of the central part is 0.05 to 3.0 mm.
Citation Information
Patent Citations
Novel polycarbonate resin
JP2000302860A
Optical lens
JP2005241962A
High-refractive-index polycarbonate resin and molding
JP2017179323A
Optical lens, and polyester carbonate copolymer for use in optical lenses
WO2011010741A1
Method for producing carbonate derivative
WO2020100977A1